International Students’ Travel Behaviour: A Cross-cultural Study of Mainland and Hong Kong Chinese in the UK - Qi, Xiao Ying (2011)
The study on consumer behaviour is popular among all industries, and tourism industry is gaining more focus. A comprehensive understanding of tourist behaviours enables the tour marketers and operators to grasp further market share.